Liberia : Does Giving People the Chance to Work Reduce Conflict and Boost Peace? - Berman, Daphna (World Bank, Washington, DC, 2015)
The evaluation found that the program successfully shifted high-risk men from criminal activities into farming. Graduates earned more money than their counterparts who weren t enrolled in the program, spent less time in illegal work and were less likely to consider fighting as mercenaries in neighboring conflicts. The evaluation also showed that skills training isn t always enough; men who received training but didn t get their start-up capital didn t do as well as those who did. As policy makers in the region look to strengthen their economies and boost stability, the results of this evaluation offer guidelines for crafting successful programs. The findings shed light on some of the constraints that youth face when trying to pursue work opportunities: Training alone may not be enough if it isn t supplemented with start-up capital.